Corruption Risk and Political Dynasties: Exploring the Links Using Public Procurement Data in the Philippines - Davis, Daniel Bruno (Archīum Ateneo, 2024)
Corruption plays a central role in underdevelopment in the Philippines, yet there is no reliable, non-aggregate, and periodic measurement for corruption in the country. This study demonstrates the use of statistical techniques to synthesize information from public procurement contracts into one indicator to measure corruption risk for each province in the Philippines from 2004 to 2018. The results show corruption risk decreased from the 2004 term to 2013, and increased to an all-time high in 2016. Regression analysis also shows that two measures of political power concentration among clans—a Hirschman–Herfindahl Index applied to the political sphere (Political HHI), and the Size of the Largest Dynasty per Province—is significantly and positively linked to the corruption risk indicator at least at the 5% significance level. This result coheres with emerging literature on political dynasties, suggesting that these debilitate checks and balances and increase the risk of impunity and malgovernance at the local level, particularly in the Philippines. This study highlights the importance of studying corruption vis-à-vis the evolving issue of political dynasties amassing power, and provides further evidence that reforms are required in this area to promote development in democracies.